Trade description act 1972: expansion of halal definition on cosmetic products / Azree Firdaus Md Amin …[et al.] - Md Amin, Azree Firdaus; Zainul Anwar, Farah Aimy; Joifin, Fara Afiqah; Kamaruddin, AzellaNatasia; Wan Zawawi, Wan Muhammad Hafiz (2010)
The definition of ‘Halal’ in the Trade Description Act 1972 only covers about food. An area of lacunae exist when Muslims in Malaysia starts to become aware of the importance of ‘Halal’ in the field of cosmetics. The rapid growth of ‘Halal’ cosmetics industry in Malaysia has paved the way to the emergence of ‘Halal’ based cosmetics lead by HP A and recently Malaysian singer icon, Datuk Siti Nurhaliza also launch her label of ‘Halal’ cosmetics under the name of 'SimplySitP. However the ‘Halal’ labeling process for cosmetics only falls under the conscience of the manufacturers because there is no specific law to making it mandatory for a cosmetic product to undergo the ‘Halal’ labeling process requirement. To attain the ‘Halal’ status before the label can be attached to the products, there are certain regulations that need to be fulfilled. First, the products must meet the criteria stipulated in Section 3 of the Trade Descriptions (Use of Expression "Halal") Order 1975 which affirm that all steps from ingredients, manufacturing and storage need to be consistent with 'Hukum Syarak'. Manufacturers will need to comply with the entire proviso before they get the grant to display ‘Halal’ label to their products. The aim in conducting this electrifying research is to put forward the significance to expand the definition of ‘Halal’ in the Trade Description Act 1972 to make it more concrete in safe guarding the security of ‘Halal’ based products used by Muslims. This study also tackles the defects of the now existing Trade Description Act 1972 focusing the Malaysian cosmetics industry. Two series of interviews have been conducted with a noted person from the Jabatan Agama Islam Selangor (JAIS). In strengthening the accuracy of the study, there are also references from books, journals, reports, articles as well as internet sources. The contributions of the study are twofold. First, to expand the provision of ‘Halal’ in the Trade Description Act 1972 which is not complete in adequacy to cover the need for ‘Halal’ labeling for cosmetics products sold in Malaysia. Secondly, Muslims will be relieved from the confusion to choose cosmetics products to be used in daily basis because the security of' Halal matters will be protected parallel with the expansion of the Act.